The Social Behavior of Adolescents Girls in Pastem Gang and Petarung LA Gang at Padang Pariaman Regency - Mufti Ali; Erianjoni Erianjoni (Science and Environmental Journal for Postgraduate, 2020)
SOCIAL BEHAVIOR OF ADOLESCENT GIRLS IN PASTEM GANG AND PETARUNG LA GANG AT PADANG PARIAMAN REGENCY *Mufti Ali1,dan Erianjoni2 1Master Program of Social Science of Universitas Negeri Padang 2Lecturer Master Program of Social Science of Universitas Negeri Padang Email : muftisos@gmail.com erianjonisosiologi@gmail.com ABSTRACT This research aims to determine the form of social behavior of adolescent girls in Pastem Gangs and Petarung LA Gangs at Padang Pariaman Regency. Location of this research are Batang Anai Sub-district and Lubuk Alung Sub-district. This research use qualitative approach with descriptive type. The data obtained through observation, interview and documentation study. The selection of informants is done by purposive sampling. Data were analyzed using Deviant Sub-cultural theory by Robert K. Merton. The result of this research are: (1) Adolescent girls background joining to Pastem Gangs and Petarung LA Gangs are: a) Family factor, b) Peer factor, c) Economy factor. (2) forms of adolescent girls social behavior in gangs are: a) Gathering until late night, b) Drink miras with all gangs member, c) Mancor (see the single organ event). (3) The position of adolescent girl in gangs are: a) Gang cash holders (treasurer), b) as an entertainer for other gangs member. Keyword: Social behavior, Adolescent Girl, Gangs